2020
DOI: 10.31235/osf.io/8hp7m
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pandemic Penalty: The gendered effects of COVID-19 on scientific productivity

Abstract: Academia provides a valuable case study for evaluating the effects of social forces on workplace productivity, using a concrete measure of output: the scholarly paper. Many academics -- especially women -- have experienced unprecedented challenges to scholarly productivity with the onset of the COVID-19 pandemic. In this paper, we analyze the gender composition of over 450,000 authorships of scholarly preprints in the preprint repositories arXiv and bioRxiv from before and during the COVID-19 pandemic. This an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 51 publications
0
24
2
3
Order By: Relevance
“…7 8 Furthermore, an analysis of science, technology, engineering and mathematics papers submitted to preprint servers concluded that women submitted publications at reduced rates during the COVID-19-associated lockdowns compared with prior years. 5 Similarly, another analysis of preprint repositories also observed a decrease in submissions by women, which was particularly pronounced among principal authors. 6 Prior studies on gender-based differences in academic productivity did not specifically study COVID-19-related publications relative to articles on other medical topics.…”
Section: Discussionmentioning
confidence: 89%
“…7 8 Furthermore, an analysis of science, technology, engineering and mathematics papers submitted to preprint servers concluded that women submitted publications at reduced rates during the COVID-19-associated lockdowns compared with prior years. 5 Similarly, another analysis of preprint repositories also observed a decrease in submissions by women, which was particularly pronounced among principal authors. 6 Prior studies on gender-based differences in academic productivity did not specifically study COVID-19-related publications relative to articles on other medical topics.…”
Section: Discussionmentioning
confidence: 89%
“…Obviously, this productivity decline will not affect all academics equally. Evidence suggests that since the beginning of the pandemic, female academics have not been submitting publications at the same pace as male academics (Amano- Patiño et al, 2020;Dolan & Lawless, 2020;Gabster et al, 2020;King & Frederickson, 2020;Vincent-Lamarre et al, 2020). Moreover, Pinho-Gomes et al (2020) found that female academics accounted for only a third of all authors who published COVID-19-related articles since January 2020 and women's representation was lower for both first and last authorship positions.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…While it is too early to fully understand the effects of the pandemic on scholarly publishing, preliminary observations have suggested that submissions to journals have generally increased during the pandemic (Bell & Fong, 2020; Squazzoni et al, 2020), likely because many researchers lost access to their laboratories for some time and switched over to writing papers (Aubry et al, 2020). However, analyses of submissions to preprint servers (Cui et al, 2020; King & Frederickson, 2020; Viglione, 2020; Vincent‐Lamarre et al, 2020) and journals (Bell & Fong, 2020; Kibbe, 2020; McCormick, 2020; Muric et al, 2020; Shurchkov, 2020; Squazzoni et al, 2020; but see Dolan & Lawless, 2020) suggest that submissions from women have either grown less than those from men, or have even declined, though the magnitude and presence of the gender difference has varied among disciplines. A decrease in the proportion of submissions authored by women suggests that the productivity of female scholars has been more substantially impacted by pandemic disruptions, compared to the productivity of male scholars, likely because many communities have closed primary schools, childcare facilities, and other public and private institutions that help manage children (Alon et al., 2020).…”
Section: Introductionmentioning
confidence: 99%